The Practice of Corporate Social Responsibility by Forestry Commission of Ghana - Parku, Kennedy Jim Edinam (UniMAC - GIJ, 2020)
The purpose of this research is to understand the various CSR activities carried by governmental organisations in Ghana and how these CSR programmes impact on the company‘s profitability. Hundred (100) questionnaires were administered by the researcher to staff of Forestry Commission Ghana, made up of top management staff, middle management staff and junior staff. Sixty (60) questionnaires were also administered to stakeholders of the organisation. Secondary data for the study were obtained from the internet, journals, financial statements of Forestry Commission Ghana and the Pearson Product Moment Correlation coefficient table was used. From the result obtained the calculated r (rc) 0.8 is greater > tabled value (rt) 0.23 thus, reject H0 and accept H1.This means that, the relationship is significant at 55% confidence level. This confirms that there is a positive relationship between Corporate Social Responsibility and profitability. From the study it was clear that most customers are not aware of CSR and even understand the meaning. The study was however, limited to finding out exactly how much in terms of monetary value CSR programmes contribute to the overall profitability ratios of the companies. For academic and industry discourse it is recommended that further study should be conducted to establish the real value in monetary terms how much CSRs contribute to the organisations profitability. Also further research should be conducted to quantify how much or to what degree these CSR programmes have impacted on the society and its corresponding value generation for the company.
THESIS